Contrasting genetic diversity and population structure among three sympatric Madagascan shorebirds: parallels with rarity, endemism, and dispersal. Issue 5 (23rd January 2015) - Eberhart‐Phillips, Luke J.; Hoffman, Joseph I.; Brede, Edward G.; Zefania, Sama; Kamrad, Martina J.; Székely, Tamás; Bruford, Michael W.
Abstract Understanding the relative contributions of intrinsic and extrinsic factors to population structure and genetic diversity is a central goal of conservation and evolutionary genetics. One way to achieve this is through comparative population genetic analysis of sympatric sister taxa, which allows evaluation of intrinsic factors such as population demography and life history while controlling for phylogenetic relatedness and geography. We used ten conserved microsatellites to explore the population structure and genetic diversity of three sympatric and closely related plover species in southwestern Madagascar: Kittlitz's plover (Charadrius pecuarius), white‐fronted plover (C. marginatus), and Madagascar plover (C. thoracicus). Bayesian clustering revealed strong population structure in the rare and endemic Madagascar plover, intermediate population structure in the white‐fronted plover, and no detectable population structure in the geographically widespread Kittlitz's plover. In contrast, allelic richness and heterozygosity were highest for the Kittlitz's plover, intermediate for the white‐fronted plover and lowest for the Madagascar plover. No evidence was found in support of the "watershed mechanism" proposed to facilitate vicariant divergence of Madagascan lemurs and reptiles, which we attribute to the vagility of birds. However, we found a significant pattern of genetic isolation by distance among populations of the Madagascar plover, but not for the other two species. These findings suggest that interspecific variation in rarity, endemism, and dispersal propensity may influence genetic structure and diversity, even in highly vagile species.